2018
DOI: 10.4236/cus.2018.62016
|View full text |Cite
|
Sign up to set email alerts
|

Configuration Mode of Ornamental Plants in Norbulingka of Tibet and Application of Landscape Color

Abstract: The application of plant landscape color has a great effect on the landscape of the scenic spot. By colorful foliage and ornamental plants with high color recognition, visitors can deepen their impressions, and thus increase the landscape aesthetic expectations and psychological recognition of the landscape sense. The plants in Norbulingka were taken as research object in this paper. Via field investigation and consulting a lot of data, color characters of ornamental plants from each genus and family were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, previous studies have found that the quality of community landscapes in a group was higher than uniformly and randomly distributed landscapes [46]. However, when investigating the degree of aggregation of landscape color patches, it was found that excessively gathered color patches may negatively affect the emotional state of people, but landscapes with more color patches are more likely to be favored by observers [32,47]. On the other hand, a colorful, attractive street edge may distract drivers, which could lead to more accidents than the "monotonous" green landscapes.…”
Section: Spatial Distribution Of Colorsmentioning
confidence: 98%
“…However, previous studies have found that the quality of community landscapes in a group was higher than uniformly and randomly distributed landscapes [46]. However, when investigating the degree of aggregation of landscape color patches, it was found that excessively gathered color patches may negatively affect the emotional state of people, but landscapes with more color patches are more likely to be favored by observers [32,47]. On the other hand, a colorful, attractive street edge may distract drivers, which could lead to more accidents than the "monotonous" green landscapes.…”
Section: Spatial Distribution Of Colorsmentioning
confidence: 98%
“…Scenic beauty has become an important evaluation index of landscape quality, and the quality of the plant color landscape directly impacts the landscape of the scenic spot [37]. Until now, studies conducted on the scenic beauty of plant color at the landscape level have mainly focused on forests and plant communities.…”
Section: Introductionmentioning
confidence: 99%